Knowledge, attitudes, and impact of COVID-19 pandemic among neurology patients in Jordan: a cross-sectional study - Athamneh, Mohammad (Egypt J Neurol Psychiatr Neurosurg, 2021)
BACKGROUND: The impacts of the COVID-19 pandemic on health services offered to patients with non-communicable diseases, including chronic neurological illnesses, are diverse and universal. We used a self-reported questionnaire to investigate these impacts on neurology patients in Jordan and assess their knowledge and attitudes towards the pandemic. RESULTS: Most respondents had positive attitudes towards the COVID-19 pandemic, with 96% reporting they believed in the seriousness of the pandemic and adhered to prevention measures. Nearly 97% resorted to the internet and media outlets for medical information about the pandemic. About one in five clinic visitors had their appointments delayed due to interruption of health services. A similar portion of patients with MS, epilepsy, and migraine or tension headache reported medication interruptions during the pandemic. One in two patients reported new events or worsening illness since the start of the pandemic, and sleep disturbances were reported by nearly one in three patients who had epilepsy or headache. CONCLUSION: The COVID-19 pandemic’s impacts on patients with neurological illnesses in Jordan were deep and diverse. Meanwhile, the majority of surveyed neurology patients demonstrated a positive attitude towards the pandemic.